2020
DOI: 10.3389/fchem.2020.00480
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Ultra-Fine Bubbles to Promoting Effect on Propane Hydrate Formation

Abstract: To investigate experimentally how ultra-fine bubbles (UFBs) may promote hydrate formation, we examined the formation of propane (C 3 H 8 ) hydrate from UFB-infused water solution using two preparation methods. In one method, we used C 3 H 8 -hydrate dissociated water, and in the other, C 3 H 8 -UFB-included water prepared with a generator. In both solutions, the initial conditions had a UFB number density of up to 10 9 mL −1 . This number density decreased by only about a half when stored at room temperature f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 28 publications
(49 reference statements)
6
28
1
Order By: Relevance
“…Based on these properties, UFBs are considered to have a long lifespan in liquids [22][23][24]. Our previous studies [18][19][20] confirmed that a large amount of UFB is formed in water when gas hydrate is dissociated. This process has also been supported by molecular dynamic simulations [25][26][27].…”
Section: Introductionmentioning
confidence: 66%
See 4 more Smart Citations
“…Based on these properties, UFBs are considered to have a long lifespan in liquids [22][23][24]. Our previous studies [18][19][20] confirmed that a large amount of UFB is formed in water when gas hydrate is dissociated. This process has also been supported by molecular dynamic simulations [25][26][27].…”
Section: Introductionmentioning
confidence: 66%
“…We used three types of liquid samples to evaluate the effect of UFBs on the promotion of CO 2 hydrate formation, as used in our previous studies [18][19][20], including deionized pure water, hydrate-dissociated water prepared by dissolving CO 2 hydrate, and CO 2 -UFB-containing water. Pure water was prepared by ion exchange (Essential Elix, Merck KGaA, Darmstadt, Germany), with a resistivity of approximately 15 MΩ cm.…”
Section: Materials and Ufb Measurementsmentioning
confidence: 99%
See 3 more Smart Citations